Tee Will of Michael Oher in John Lee Hancock's The blind Side Movie (2009) : An Existentialist Approach - SAPUTRA, ANJAR DENY (2011)
The major problem of this study is to reveal the will ofMichael Oher inThe Blind Side(2009) movie. The objective of this study is to analyze the movie based on its structural elements and based on Existentialist approach. In analyzing The Blind Side(2009), the writer uses qualitative method and Existentialist approach. The object of the study is the theme that played by all characters inThe Blind Side movie published in 2009, written, co-produced, and co-edited byJohn Lee Hancock. The primary data source is the script, and the secondary data sources are the other data related to the analysis such as the author's biography and some reference books. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive analysis. The findings of the study show that, The Blind Side Movie illustrates the will of Michael Oher. The writer explores the movie with Existentialist approach. The writer uses Sartre's theory of existentialism which are included of Being, Existence Precedes Essence, Consciousness (cogito), Freedom to Choose, Anxiety, Transcendence of Ego, and Nothingness. The character of Michael Oher is shown in the terms above. His will is described very well by John Lee Hancock in this movie by showing the Michael Oher Existence.